Improving English Pronunciation Skills by Using English Phonetic Alphabet Drills in EFL Students - Warinthon Dandee,; Pornchai Pornwiriyakit, (Journal of Educational Issues, 2024)
This study aims to investigate the improvement of EFL students’ English pronunciation skills by using English phonetic alphabet drills. The samples of this study were 35 first-year students of English for International Communication major, Faculty of Humanities and Social Sciences, Rajamangala University of Technology Tawan-ok. They all registered for the English Pronunciation subject in the second semester. The instruments used for collecting data were English phonetic alphabet drills, English phonetic alphabet collecting forms, observation and focus group interview questions. The data were analyzed both statistically and descriptively. The results showed that all students were able to pronounce English consonant and vowel sounds more accurately after applying English phonetic alphabet drills. However, Nasal /m, n, ŋ/in the final position, and /l/ in the initial and medial position were still the problematic consonant sounds including central vowels, /ʌ/ and /ə/, and the back vowels, /ɒ/, /ʊ/, /u/ and /əʊ/. Students also had difficulties pronouncing voiced sounds. The causes of pronunciation errors were due to differences in the phonological system of the languages, mother tongue interference, and English spelling and pronunciation. From the findings, it was clear that the English phonetic alphabet knowledge could help student improve their English pronunciation.